SEREN TAUN SEBAGAI PONDASI PERTAHANAN TOLERANSI PADA MASYARAKAT CIGUGUR KUNINGAN - Chandra Lesmana; Elly Malihah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
Tolerance is as one of basic capitals the Indonesians should have as an attempt of building peaceful and harmonious life between religious communities. This research was conducted based on an objective to find out how the people of Cigugur Kuningan can live adjacently and peacefully without either conflict or dispute amid plural community condition. Different religious backgrounds the people of Cigugur Kuningan are not something that can make them divided, but are defined as a driving force of progress and benefit for the people of Cigugur of Kuningan Regency, West Java. This research employed literature research/narrative research technique, in which data was collected based on the result of observation on previous studies related to tolerance in Cigugur people, concluding that Cigugur people, with different creed and religion backgrounds can live adjacently and peacefully. It was initiated with the presence of blood ties and Seren Taun tradition held by Cigugur people as a foundation of religious tolerance defense within them.